Evaluation of appropriate follow-up after curative surgery for patients with colorectal cancer using time to recurrence and survival after recurrence: a retrospective multicenter study - Yamano, Tomoki (Oncotarget, 2018)
INTRODUCTION: The follow-up schedule for colorectal cancer patients after curative surgery is inconsistent among the guidelines. Evaluation of time to recurrence (TTR) and survival after recurrence (SAR) may provide evidence for appropriate follow-up. METHODS: We assessed 3039 colon cancer (CC) and 1953 rectal cancer (RC) patients who underwent curative surgery between 2007 and 2008. We evaluated the pre- and post-recurrent clinicopathological factors associated with TTR and SAR in each stage of CC and RC. RESULTS: The recurrence rates of stages I, II, and III were 1.2%, 13.1%, and 26.3%, respectively, for CC, and 8.4%, 20.0%, and 30.4%, respectively, for RC. In CC patients, high carcinoembryonic antigen (CEA) level and lymphovascular invasion were independent predictors of short TTR. In RC patients, metastatic factors (liver metastasis in stage III) and venous invasion (stage III) were independent predictors of short TTR. The prognostic factors of SAR were age (stage II CC and stage III RC), female gender (stage III RC), high CEA level (stage II RC), histological type (stage III CRC), nodal status (stage III CC), recurrence within 1 year (stage III RC), M1b recurrence (stage II CRC), local recurrence (stage II CC), and no surgical resection after recurrence (stage II and III CRC). CONCLUSIONS: The follow-up schedule for stage I should be different from that for the other stages. We recommend that intensive follow-up is appropriate in stage III CC patients with undifferentiated adenocarcinoma or N2 nodal status, stage II RC patients with high preoperative CEA level, and stage III RC patients.